2002
DOI: 10.1902/jop.2002.73.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix Allografts to Achieve Increased Attached Gingiva. Part 2. A Histological Comparative Study

Abstract: The results of this 6-month histological evaluation suggest that: 1) the resultant tissue types of ADM grafts were similar to "scar" tissue; 2) the non-vital dermal matrix of ADM allograft lacked the capability of directing cyto-differentiation of the covering epithelium; 3) autogenous FGG-derived tissue was neither identical to donor palatal mucosa nor to adjacent gingiva propria; 4) the connective tissue of donor palatal mucosa only partially contributed to the differentiation of the epithelium covering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 24 publications
3
101
1
4
Order By: Relevance
“…Vital bone, connective tissue and marrow, and residual graft particles were reported as a percentage of the total core. The mean vital bone was 34.5% (AH with ADMA), 41.7% (ABB with ADMA), 27 and did not result in any increased bone-to-implant contact. 19,20 Recently, an acellular dermal matrix allograft (ADMA) was introduced as a substitute for autogenous connective tissue grafts for various periodontal, peri-implant, and extraction socket treatments.…”
mentioning
confidence: 87%
“…Vital bone, connective tissue and marrow, and residual graft particles were reported as a percentage of the total core. The mean vital bone was 34.5% (AH with ADMA), 41.7% (ABB with ADMA), 27 and did not result in any increased bone-to-implant contact. 19,20 Recently, an acellular dermal matrix allograft (ADMA) was introduced as a substitute for autogenous connective tissue grafts for various periodontal, peri-implant, and extraction socket treatments.…”
mentioning
confidence: 87%
“…Studies evaluating esthetics using ADM generally show better esthetics in comparison with free gingival grafts [47][48][49] and similar esthetics in comparison with connective tissue grafts. 38,50,51 Although, there is currently no gold standard regarding soft tissue grafting at periimplant sites after definitive crown placement, the connective tissue graft served as the control in our study because of excellent results reported in many systematic reviews for natural tooth application.…”
Section: Esthetic Parametersmentioning
confidence: 99%
“…Generally, ADM is associated with longer incorporation and healing periods than the SCTG around natural teeth. [68][69][70] However, this finding has not been evaluated around implants. Additionally, ADM is thought to heal in a scarlike tissue due to its: (1) inability to cytodifferentiate the epithelial layer, 70 (2) lack of cellular and vascular components, and (3) lack of connective tissue organization, and keratinization of overlying alveolar mucosa.…”
Section: Patient Parametersmentioning
confidence: 99%
“…Por otra parte, para el tratamiento del aumento de encía queratinizada, existe una tendencia de mayor formación de tejido queratinizado con el ITCS en comparación con MDA (7,8) . La misma tendencia se observa pero en menor tamaño entre MDA y IGL (1) .…”
Section: Discussionunclassified
“…Se ha demostrado la biocompatibilidad de este material y se ha concluido que la MDA no tiene mucha capacidad de inducir cito diferenciación (8) . Sin embargo, esto no sería relevante ya que esta propiedad se atribuye más al microambiente tejido conectivo/epitelio de la zona receptora.…”
Section: Estudios Histológicos De Matriz Dérmica Acelularunclassified